Сoronary artery disease mortality rates in the Russian Federation and a number of regions: dynamics and structure specifics - D. Sh. Vaisman; E. N. Enina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the dynamics and structure of coronary artery disease (CAD) mortality rates in the Russian Federation (RF) and a number of regions.Material and methods. The study analyzed the dynamics of the mortality structure and the reliability of CAD mortality rates in the Russian Federation and a number of regions before and during the coronavirus disease 2019 (COVID-19) pandemic. For the analysis, statistical data of the Russian Ministry of Health and Rosstat C52 tables for 2019-2022 were used. The study used statistical and analytical methods. MSOffice Excel 2019 was used for data processing. The correct coding of death causes was determined by expert analysis.Results. In the Russian Federation and the regions studied in 2019-2022, there was no general trend due to territorial differences in the dynamics of CAD mortality rates and the proportion of acute and chronic CAD forms. An expert assessment in the studied Russian regions revealed errors in the preparation of medical certificate of cause of death. A decrease in the proportion of acute CAD types was noted in the Russian Federation as a whole, as well as in the Samara, Kaliningrad, and Tula regions, and an increase in the Belgorod and Tomsk regions. A decrease in the proportion of chronic CAD forms was noted in the Tula region, and an increase in the Russian Federation as a whole, Samara, Kaliningrad, Tomsk and Belgorod regions. An expert assessment in the studied regions revealed the following peculiarities in death certificates: the proportion of certificates with three completed lines of part 1 of paragraph 22 ranges from 11,1 to 30,3%.Conclusion. The high CAD mortality rate in the studied regions is associated mainly with errors in the selection of chronic CAD forms as the initial cause of death. Differences in mortality rates from CAD in a number of regions are associated with the incorrect selection, most often, of chronic forms as the initial cause of death before and after the COVID-19 pandemic.